Efficacy and safety of erythrocytapheresis and low‐dose erythropoietin for treatment of hemochromatosis. Issue 3 (8th June 2016) - Brückl, Dorothea; Kamhieh‐Milz, Sundrela; Kamhieh‐Milz, Julian; Salama, Abdulgabar
Abstract : Background: The aim of this study was to determine retrospectively the efficacy of combined therapy using erythropoietin (EPO) and erythrocytapheresis (EA) in patients with hereditary hemochromatosis (HH) who did not tolerate phlebotomy. Patients and Methods: Twenty patients (age range, 43–74 years) with genetically confirmed HH had received low‐dose EPO (4, 000 IU) in accordance to the patient's hemoglobin levels between each EA session. Laboratory parameters including hemoglobin, ferritin, transferrin, and iron were measured at regular intervals. Results: Anemia did not occur in a single patient and no serious side effects were observed. Combined treatment with EPO and EA was well tolerated, and all 18 patients who suffered from fatigue prior to therapy recovered. Median ferritin values were 678.5 ng/L before treatment and 145 ng/L after treatment. Conclusion: EA in combination with EPO is safe and effective in treating patients with HH. Prospective studies comparing this therapeutic option to phlebotomy are warranted. J. Clin. Apheresis 32:170–174, 2017. © 2016 Wiley Periodicals, Inc.